Experimental study of Peltier-Based Thermoelectric Cooling Box System - Rosdi Ab Rahman; Mahmod Abd Hakim Mohamad; Masiri Kaamin; Mohd Faizal Mohideen Batcha; Mohammad Daniel Aiman Mazlan; Muhammad Luqman Rosli; Mohamad Azrul Arif Che Aziz (Journal of Advanced Research in Applied Mechanics, 2022)
Thermoelectricity especially the Peltier concept can be one of the useful alternatives for the refrigeration system. The refrigeration systems nowadays which are based on vapour compression cycles are less environmentally friendly. This paper presents a Peltier-based thermoelectric cooling box and its functionality as a cooling mechanism. The activities involved in developing this system are designing the product using CAD applications, producing electrical circuits, and experimental analysis to evaluate the system’s performance. The material used is the Peltier module, CPU fan, polystyrene box and, some other materials in producing a mini thermoelectric cooling box. The experimental data showed proved the system’s cooling capabilities to function as a cooling box over a specific duration when tested with and without a canned beverage to simulate as products to be cooled. Overall, the temperature drops faster when there are no beverages in it with an average temperature difference of 4.86 C after 90 minutes for both conditions. In addition, some improvements can be done to the product in many aspects especially on its cooling capabilities. The Peltier can be added for maybe one or two more in parallel connections which can improve its cooling capabilities.